2018
DOI: 10.1016/j.physbeh.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Profiling caregivers: Hormonal variation underlying allomaternal care in wild red-bellied lemurs, Eulemur rubriventer

Abstract: Neuroendocrine evidence suggests that paternal care is mediated by hormonal mechanisms, where hormonal changes in expectant and new fathers facilitate infant care. In species with obligate and extensive paternal care such as humans, androgen levels decline once males are paired and have offspring, and in direct response to offspring care. Facultative infant care is widespread in the Order Primates, but the underlying hormonal mechanisms are largely unknown. We found that wild, red-bellied lemurs living in fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 127 publications
0
27
0
Order By: Relevance
“…Some studies yielded no effect of habitat (Rakotoniaina et al , 2016; Rimbach et al , 2013), while others found lower glucocorticoids in disturbed habitat (e.g. artiodactyls: Sayre (1996); caudates: Homan et al (2003); primates: Aronsen et al (2015); Tecot (2008, 2013); proboscids: Munshi-South et al (2008)), and in populations subjected to a chronic stress regime (Cyr and Romero, 2007). While low glucocorticoids can indicate low levels of stress, they may also indicate tolerance, habituation, attenuation or cessation of the adaptive stress response (Herman, 2013; Homan et al , 2003; Mendoza et al , 2000; Romero, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies yielded no effect of habitat (Rakotoniaina et al , 2016; Rimbach et al , 2013), while others found lower glucocorticoids in disturbed habitat (e.g. artiodactyls: Sayre (1996); caudates: Homan et al (2003); primates: Aronsen et al (2015); Tecot (2008, 2013); proboscids: Munshi-South et al (2008)), and in populations subjected to a chronic stress regime (Cyr and Romero, 2007). While low glucocorticoids can indicate low levels of stress, they may also indicate tolerance, habituation, attenuation or cessation of the adaptive stress response (Herman, 2013; Homan et al , 2003; Mendoza et al , 2000; Romero, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important when causal relationships are difficult to determine, as is the case with many endangered species for whom experimentation would be inappropriate. In addition to measuring baseline levels, the responses of individuals in disturbed and undisturbed habitat to known stressors, such as food scarcity (Cavigelli, 1999; Gómez-Espinosa et al , 2014; Muller and Wrangham, 2004), also should be compared; this can help distinguish between healthy, low glucocorticoid levels that fluctuate in response to challenge, and an attenuated response reflecting an inability to cope in the same way (Tecot, 2008, 2013). Finally, when possible, data on fitness measures should be collected (Beehner and Bergman, 2017; Bonier et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNP is approximately 41,000 ha of rainforest located in southeastern Madagascar (E47°18'–47°37', S21°02'–21°25'). There has been intermittent research on red‐bellied lemurs in RNP beginning in the 1980s (Durham, ; Jacobs, ; Merenlender, ; Overdorff, ; Tecot, ), and the characterization of this species' social system (pair‐living, pair‐bonded, monogamous) is based on data from this population (e.g., Merenlender, ; Overdorff, ; Overdorff & Tecot, ; Tecot et al, ). Red‐bellied lemurs exhibit a fairly strict birth season (August/September/October), with out‐of‐season births occurring rarely, and males often provide care to infants (Overdorff & Tecot, ; Tecot, ).…”
Section: Methodsmentioning
confidence: 99%
“…), and that prolactin may be upregulated with paternal care to a similar degree that testosterone is downregulated (Gettler, Kuo, and Agustin Bechayda )—together providing additional evidence for endocrine mediation of mating and parental effort in male human. Conversely, Tecot and Baden () observed that among male red‐bellied lemurs, fecal androgen levels were negatively associated with paternal carrying but positively associated with total allomaternal care behavior, which included protective behaviors such as grooming and huddling. Differences in androgen levels were unlikely to reflect mating effort, as this species exhibits long‐term pair bonds and nonoverlapping seasons of infant care and breeding, suggesting that protective paternal behaviors can coexist with postnatally elevated androgen levels.…”
Section: Relational Dynamics Influencing Biology and Behaviormentioning
confidence: 99%